Story Sharing : model of collective collaboration in online museum environment - Miklošević, Željka; Zlodi, Goran; Babić, Darko muzeolog (2011)
The need for a more pronounced role of museums in today’s democratic and heterogeneous society has led to a change of the institutional framework which have now come to include voices of all those who have been underrepresented in museums. The new museum needs to pluralize the range of possible meanings by accepting views and interpretation not only of curators but museums users as well. However, museums have been reluctant to adopt new approaches in their work. The paper therefore suggests a more acceptable, on-line model which allows for multivocal interpretations of museum material by connecting the museum data base and web 2.0 applications. The usual repository of actions facilitated by on-line social networks is mostly reserved for web sites outside the direct museum’s digital realm. Conversely, the web service presented in this paper supports participative activities on the very museum web site by allowing users to engage with museums’ collection. The collection in the form of a digital catalogue can thus serve either as a source or inspiration for individual interpretation. Both choosing museum objects from the on-line catalogue and publishing extra-museum material in different media in order to contextualize the object and create stories builds a two- way communication between curators and actively participating users which is presented to all other types of online users. User-generated content is here seen as a possible influence on the actual institutional policies, namely, collecting, research, exhibiting practices, giving relevance to certain topics etc. By allowing active participation in the creation of meaning, de-authorizing the museum, and at the same time creating a massive depository of heritage information, this model contributes to the paradigmatic shift that has been indicated in the museum world in the last ten years.
Projekt MZOS
ENG